The Dietary Cation Anion Balance Exacerbates the Effects of Inorganic Phosphates on Parameters of Phosphate Metabolism in Cats - C, Steffen; B, Dobenecker (Journal of Veterinary Healthcare, 2024)
Dietary intake of inorganic phosphates is linked to various adverse health effects. Excessive intake of highly soluble inorganic phosphates, which are used as feed and food additives, have been found to impair parameters of kidney health. As chronic kidney disease represents one of the most frequently occurring terminal diseases especially in cats, extensive knowledge regarding the safety of these additives is important. Other minerals, such as calcium, can modulate their effects on the phosphate homeostasis and kidney health. Therefore, it is crucial to examine further factors, such as the dietary cation-anion balance (CAB), resulting from the concentrations of major minerals in a diet. In this study, eleven healthy cats were fed a control diet and two diets with added sodium monophosphate (NaH2PO4) with either a low (-10 mmol/kg dry matter) or high (+450 mmol/kg dry matter) CAB for 28 days each. The serum concentrations of phosphate and parameters of phosphate homeostasis were determined in the fasting and postprandial blood samples next to the apparent digestibility and retention of phosphate and calcium. The diet with positive CAB led to an increase of serum phosphate and the phosphatonin FGF23, apparently digested phosphate, and phosphate retention. This is further proof that source and amount of phosphates in a diet are not the only determinants of the extent of potential adverse health effects. Until the interactions between inorganic phosphates and other dietary compounds are fully understood, recommendations regarding the safe use of phosphate containing additives in pet food are precarious.
Keywords: Inorganic Phosphates; Chronic Kidney Disease; Phosphate Homeostasis; Dietary Cation-Anion Balance; Cats